Effect of heat-moisture treated brown rice crackers on postprandial flow-mediated dilation in adults with mild endothelial dysfunction. Issue 8 (August 2022) - Watanabe, Kenichi; Hirayama, Masao; Arumugam, Somasundaram; Sugawara, Masayoshi; Kato, Hisanori; Nakamura, Sumiko; Ohtsubo, Ken'ichi; Matsumoto, Hitoshi; Nomi, Yuri; Homma, Noriyuki; Fujii, Yoshifumi; Murohashi, Naoto; et al.
Abstract: Background: Endothelial dysfunction is an early pathophysiological feature and independent predictor of a poor prognosis in most forms of cardiovascular disease. We evaluated the effect of brown rice crackers (BR-C) on endothelial function. Methods: Effect of heat-moisture treated (HMT) -BR-C on postprandial flow-mediated dilation (FMD) in adults with mild endothelial dysfunction was compared with that of BR-C and white rice crackers (WR-C) in 12 adults with mild endothelial dysfunction (less than 7.0% of FMD) by a randomized, single-blind, three-treatment three-period crossover trial (UMIN 000034898). Since we considered that the FMD increase was associated with the treatment of HMT-BR-C, we examined the effect of three possible factors: postprandial glucose levels, polyphenol content, and polyphenol release from the food matrix. Results: Mean pre-intake baseline FMD values of HMT-BR-C, BR-C, and WR-C were 4.9%, 5.1%, and 4.9%, respectively, and those values 1 h post-intake were 6.3%, 5.1%, and 4.8%, respectively. There was no difference in intergroup comparisons of FMD using Dunnett's multiple comparison test. There was a significant increase in FMD only in HMT-BR-C in intragroup comparisons ( P = 0.042 by paired- t test). In comparison with BR-C, no significant difference was noted in the postprandial glucose level nor in the content of total polyphenols and ferulic acid derivatives in HMT-BR-C. However, the 70% ethanol extracted from HMT-BR-C contained a significantly larger amount of free and bound ferulic acids than from BR-C. Conclusion: HMT-BR-C intake increased the postprandial FMD response. Abstract : Crossover trial, Heat-moisture treated (HMT) brown rice cracker, Flow-mediated dilation (FMD), Polyphenols, Blood glucose.